2019
DOI: 10.1016/j.knosys.2019.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Towards reliable online clickbait video detection: A content-agnostic approach

Abstract: Online video sharing platforms (e.g., YouTube, Vimeo) have become an increasingly popular paradigm for people to consume video contents. Clickbait video, whose content clearly deviates from its title/thumbnail, has emerged as a critical problem on online video sharing platforms. Current clickbait detection solutions that mainly focus on analyzing the text of the title, the image of the thumbnail, or the content of the video are shown to be suboptimal in detecting the online clickbait videos. In this paper, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…From the analysis, it has been observed that random forest found to be the best classifier, with an accuracy of 91.16%. Whereas, [ 7 ] developed a novel content-agnostic scheme for effectively detecting the clickbait video by exploring and analyzing the comments from the viewers. Along with the machine learning technique, some of the researchers have also explored the deep learning methods.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…From the analysis, it has been observed that random forest found to be the best classifier, with an accuracy of 91.16%. Whereas, [ 7 ] developed a novel content-agnostic scheme for effectively detecting the clickbait video by exploring and analyzing the comments from the viewers. Along with the machine learning technique, some of the researchers have also explored the deep learning methods.…”
Section: Related Workmentioning
confidence: 99%
“…The self-generated dataset[MVD] has been proposed in this paper, which further helps to explore the research in this field. Few methodologies have been proposed that aims to detect clickbait video [ 7 ]. This is an emerging field and largely unsolved problem, due to which still very few works have been reported in this area.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent survey of social sensing can be found in [1]. Social sensing has been widely used in environment sensing [12], traffic monitoring [22], emergence and disaster response [23], social sensor profiling [24], point-of-interest (POI) identification [25], clickbait video detection [26], and abnormal event identification [27]. Quality-cost-aware optimal task allocation in social sensing remains to be an open challenge that has not been fully addressed [3].…”
Section: Social Sensingmentioning
confidence: 99%